2014
DOI: 10.1037/a0032698
|View full text |Cite
|
Sign up to set email alerts
|

Mental toughness, social support, and athletic identity: Moderators of the life stress–injury relationship in collegiate football players.

Abstract: In this study, we examined the moderating effects of social support, athletic identity, and mental toughness on the life stress–injury relationships in a sample of 92 NCAA Division I-A football players from an intact team. Hierarchical regression analyses revealed that there were no significant main effects of positive or negative life stress, social support, athletic identity, and mental toughness on injury outcome. However, significant interaction effects with positive life stress were found for family socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
1
8

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 45 publications
3
29
1
8
Order By: Relevance
“…Indeed, the results of the study show that in the group of players, those who had suffered an injury showed significantly lower stress values than those who had not been injured, results that are not in agreement with what is found in the majority of previous studies [9,26,32], and are not predicted exclusively by the Andersen and Williams model [13,14].…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…Indeed, the results of the study show that in the group of players, those who had suffered an injury showed significantly lower stress values than those who had not been injured, results that are not in agreement with what is found in the majority of previous studies [9,26,32], and are not predicted exclusively by the Andersen and Williams model [13,14].…”
Section: Discussioncontrasting
confidence: 40%
“…Second, research has been also centered on how some variables can mediate the relationship between the level of perceived stress and the injury, such as in the case of the competitive anxiety, depression, coping strategies, social support, etc. [26,27]. However, the results have not always been coincident, and are even sometimes contradictory.…”
Section: Introductionmentioning
confidence: 94%
“…4 support (Petrie, Deiters, & Harmison, 2014) and risk-taking behavior (Bovard, 2008) have been shown to be related to vulnerability to sports injuries.…”
Section: Social Running Head: a Pilot Stress-management Program To mentioning
confidence: 99%
“…Dentro de las dimensiones probables de factores de riesgo asociados se encuentran los factores psicosociales. Éstos se han convertido en un área de gran interés en la investigación de las dos últimas décadas, llegando a ocupar un rol significativo tanto para explicar la ocurrencia de lesiones, como para comprender mejor el proceso de recuperación de las mismas (Almeida et al, 2014;Fernandes et al 2014;Johnson e Ivarsson, 2011;Maddison y Prapavessis, 2005;Petrie, Deiters y Harmison, 2014).…”
Section: Introductionunclassified